Penguatan Literasi Pemasaran Digital Pengrajin Emping Melinjo - Susi Indriyani; Pipit Novilasari; Desi Derina Yusda; Dwi Silvia; Adhi Nurhartanto (Jurnal Abdimas Multidisiplin, 2026)
Purpose: This community service program aims to enhance digital marketing literacy among emping melinjo artisans in Bernung Village, Pesawaran Regency, by strengthening their understanding of basic marketing management and the effective use of social media as a marketing tool to support micro-enterprise digital transformation. Research Methodology: The program employed a Participatory Action Research (PAR) approach involving 25 active emping melinjo artisans. Activities were conducted through sequential stages, including initial assessment (pre-test), training on marketing management concepts (segmentation, targeting, positioning, and branding), hands-on digital marketing workshops using social media platforms, mentoring, and final evaluation (post-test). Quantitative analysis was applied using paired sample comparisons to assess changes in participants’ literacy levels. Results: The results indicated a statistically significant improvement in the participants’ digital marketing literacy, with the average score increasing from 50 in the pre-test to 85 in the post-test. Participants demonstrated improved market-oriented thinking and successfully applied the training outcomes by creating business-related social media accounts and producing basic promotional content. Conclusions: The program effectively strengthened digital marketing literacy and facilitated a shift from production-oriented practices to market-oriented strategies among traditional food micro-enterprises. Limitations: The primary limitation lies in the relatively short mentoring period (17-22 November 2025), which restricts the measurement of long-term economic impacts, such as revenue growth and market expansion. Contributions: This program contributes practically by empowering rural microenterprises to adopt digital marketing strategies and academically by offering a replicable community-based model for enhancing digital marketing literacy in post-pandemic contexts.